Leitura das concentrações de sódio e açúcar a partir de rótulos em produtos geralmente consumidos no dia a dia: uma aplicação no ensino de Química - SANTOS, Ricardo Rafael Sousa dos (2023)
This work refers to an exhibition held at the E.E.E.F.M Luiz Nunes Direito school, with the aim of discussing the high concentrations of sodium and sugar in some products generally consumed on a daily basis, and raising awareness among visitors about the dangers of consuming too much. these ingredients. Furthermore, the aim of the work was also for students to understand the content related to concentrations of solutions through this work. In general, it is possible to state that the work carried out contributed to raising the interviewees from a lower level to a level of more knowledge on the subject. In addition to instilling more conscious consumption by recognizing the concentration of salt and sugar in industrialized products present in everyday life.